The prevalence of optrA-carrying Enterococci in the vaginal micro-ecology of pregnant women in late pregnancy - Yanjun Xie; Fangyi Xu; Huali Dong; Jianfeng Mao; Chuanling Zhang (Microbiology Spectrum)
ABSTRACT The colonization of Enterococcus in the female vagina leads to neonatal and pediatric enterococcal septicemia. Linezolid (LZD) is a kind of mainstream drug for treating multidrug-resistant Gram-positive infections. OptrA is the main LZD-resistance gene at Enterococci in human isolates. It is essential to explore the prevalence of optrA-carrying Enterococcus in vaginal secretions of late pregnant women and the drug resistance of optrA. From May to June 2023, this study recruited 340 volunteers in late pregnancy (35–40 weeks of pregnancy) to provide non-repetitive vaginal discharge samples. Luria-Bertani broth and florfenicol (10 µg/mL) were used to enrich bacteria. Enterococci was identified through time-of-flight mass spectrometry. Additionally, antimicrobial susceptibility, polymerase chain reaction, and next-generation sequencing assays were applied to this study. Fifty-four optrA-carrying Enterococcus strains were obtained, the proportion of the whole vagina of late pregnant women was 15.88% (54 out of 340), and Enterococcus faecalis account the highest proportion. All optrA-carrying Enterococcus were resistant to at least three drugs. Tetracycline, chloramphenicol, erythromycin, and LZD have higher bacterial resistance rates. Genetic environment analysis revealed that IS1216E, fexA, and erm(A) may synergistically exert multidrug resistance with optrA. It is necessary to strengthen the surveillance of optrA-carrying Enterococcus in pregnant women. This study provides scientific support for controlling hospital infections and managing antibiotic-resistant bacteria, and provides a scientific basis for rational clinical medication.IMPORTANCEThe disruption of cervicovaginal microbiota homeostasis is considered a key factor in causing imbalance in the microenvironment, leading to inflammation, transmission of infections, and illness. Enterococcus is considered a major cause of healthcare-related infections globally. It has resistance to multiple antimicrobial drugs, which pose significant challenges for clinical treatment. Therefore, it is crucial to assess the prevalence of optrA-carrying Enterococcus in vaginal secretions of late pregnant women and the drug resistance of optrA. This study detected 15.88% of optrA-carried Enterococci in 340 pregnant women. Furthermore, we found that optrA-carrying Enterococcus strains are highly resistant to tetracycline, chloramphenicol, erythromycin, and Linezolid. Additionally, genetic environment analysis revealed that IS1216E, fexA, and erm(A) may synergistically exert multidrug resistance with optrA. This study provides scientific support for controlling hospital infections and managing antibiotic-resistant bacteria and provides a scientific basis for rational clinical medication.